TREN PENELITIAN GLOBAL DALAM CIVIC AND CITIZENSHIP EDUCATION: SEBUAH STUDI BIBLIOMETRIK - Wasilah, Wasilah; Matroni, Matroni; Ikmal , Moh (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This study aims to identify the development of research on Civic and Citizenship Education (CCE) over the past three decades and to explore future research directions. The study addresses a gap in the existing literature, which has yet to comprehensively map thematic trends, institutional affiliations, and contributions from developing countries in the field of CCE. A bibliometric approach was employed using data from the Scopus database, analyzing 1,444 articles published in reputable academic journals, with the assistance of Biblioshiny and VOSviewer tools. The results indicate that CCE has gained increasing global attention, predominantly from countries with well-established education systems. Indonesia ranks seventh with 109 publications, yet no Indonesian institution appears among the top ten affiliations, highlighting opportunities for Indonesian scholars to enhance their contributions. The study also identifies emerging themes such as the digitalization of civic education, the role of social media, and inclusive approaches. This research is expected to provide new directions for the development of civic education policies and practices at the global level. ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi perkembangan penelitian civic and citizenship education (CCE) selama tiga dekade terakhir dan mengeksplorasi arah penelitian di masa depan. Studi ini mengisi kesenjangan dalam literatur sebelumnya yang belum secara komprehensif memetakan tren topik, afiliasi institusi, dan kontribusi negara-negara berkembang dalam bidang CCE. Metode yang digunakan adalah pendekatan bibliometrik dengan data dari database Scopus, menganalisis 1.444 artikel yang diterbitkan di jurnal akademik bereputasi, dengan bantuan perangkat Biblioshiny dan VOSviewer. Hasil menunjukkan bahwa CCE semakin mendapat perhatian global dengan dominasi dari negara-negara dengan sistem pendidikan mapan. Indonesia berada di peringkat ke-7 dengan 109 publikasi, namun tidak ada institusi Indonesia dalam 10 besar afiliasi teratas. Hal ini menunjukkan peluang peningkatan kontribusi akademisi Indonesia. Studi ini juga menemukan tren topik seperti digitalisasi pendidikan, peran media sosial, dan pendekatan inklusif. Penelitian ini diharapkan dapat memberikan arah baru bagi pengembangan kebijakan dan praktik pendidikan kewarganegaraan secara global.